TV show helps mobilize East African farmers to adopt climate-smart agriculture - CGIAR Research Program on Climate Change, Agriculture and Food Security (2016)
Shamba Shape Up is an East African TV show that helps smallholders ‘make over’ their farms by providing help with recurrent agricultural challenges such as lack of water, pests and diseases, crop production and reaching markets. Using knowledge from CCAFS, CGIAR Centers, and numerous development partners, the show is increasingly presenting climate-smart agriculture (CSA) to East African smallholders—airtime dedicated to CSA is up to 35% of total programme time. The number of average viewers per month is over 9 million, 42% of which (over 5.5 million smallholders in 2014) have adopted new practices, boosting Kenya’s gross domestic product (GDP) by over USD 24 million in the maize and dairy sectors.